2023
DOI: 10.2105/ajph.2023.307301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Public Health Contact Tracing for Mpox Among Gay, Bisexual, and Other Men Who Have Sex With Men—10 US Jurisdictions, May 17–July 31, 2022

Abstract: Objectives. To examine the potential impact of contact tracing to identify contacts and prevent mpox transmission among gay, bisexual, and other men who have sex with men (MSM) as the outbreak expanded. Methods. We assessed contact tracing outcomes from 10 US jurisdictions before and after access to the mpox vaccine was expanded from postexposure prophylaxis for persons with known exposure to include persons at high risk for acquisition (May 17–June 30, 2022, and July 1–31, 2022, respectively). Results. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…We identified three studies meeting the inclusion criteria for question 1 (see Table 1 ). One retrospective observational study conducted in the US [ 16 ] examined contact tracing, while the other two cross-sectional studies [ 17 , 18 ] investigated specific sexual behaviours. All three studies included exclusively male participants, predominantly MSM, who self-reported their sexual behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified three studies meeting the inclusion criteria for question 1 (see Table 1 ). One retrospective observational study conducted in the US [ 16 ] examined contact tracing, while the other two cross-sectional studies [ 17 , 18 ] investigated specific sexual behaviours. All three studies included exclusively male participants, predominantly MSM, who self-reported their sexual behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Cope et al. [ 16 ] investigated the effectiveness of contact tracing in curbing mpox transmission among MSM, particularly after the expansion of access to mpox vaccines. They found a significant reduction in proportion of MSM with mpox who provided location details for their sexual contacts after the vaccination campaign began.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Contact tracing is one of the tools used to control infectious disease outbreaks like mpox. [7][8][9][10] Its purpose is to identify and isolate new cases to interrupt transmission chains. Moreover, persons who have been exposed to a case or are likely to be exposed in the future based on risk factors can be identified through contact tracing and offered prevention strategies, such as risk reduction counseling, vaccination, and postexposure prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…The legally binding International Health Regulations (IHR) 2005 require countries to have the ability to detect, report, and respond to infectious health threats 6 . Contact tracing is one of the tools used to control infectious disease outbreaks like mpox 7‐10 . Its purpose is to identify and isolate new cases to interrupt transmission chains.…”
Section: Introductionmentioning
confidence: 99%